The Influence Of The @Ikom_Telu Instagram Account Strategy In Fulfilling The Information Needs Of Telkom University Communications Science Students - Pratama, Okta Andika; Putri, Idola Perdini (eProceedings of Management, 2025)
Indonesia, a global population leader, experiences a surge in digital technology use. Datareportal.com's "Digital 2024Indonesia" confirms rising internet user activity. This study investigates the impact of using the social media platformInstagram @ikom_telu on fulfilling information needs for Telkom University communication science students. The researchanalyzes social media use (context, communication, collaboration, connection) and information needs (current, daily,exhaustive, catching-up) through a quantitative descriptive survey with 301 Telkom University communication sciencestudents. The findings reveal a positive and significant influence of social media use on information needs. This suggeststhat effectively using Instagram @ikom_telu as a communication platform enhances students' information needs. Futureresearch can explore different methodologies and broader sample populations. This study demonstrates the potential ofsocial media in addressing information needs, encouraging responsible and effective use for educational benefit Keywords- Instagram, Activity Content , Activity Content Information Needs